Evaluating Measurement Model for values inculcation in Mathematical Contents Delivery - Liman, Mukhtar Alhaji; Ibrahim, Mohd Burhan; Gana, Iya Aliyu (International Research Journals, 2013)
A value based educational system is an integral part of human intellectual development. This is because knowledge acquired and valued tends to remain in the learners’ memory longer than procedural knowledge. As such, this study aims to examine the constructs of values inculcation in mathematics teaching and learning in order to ascertain the extent to which the conceptualized measure for the inculcation of mathematical values reproduces the data. The study also evaluates the adequacy of the inculcation framework across mathematics teachers’ gender and academic qualifications. Data was collected from a self-reported questionnaire administered to (n=509) secondary schools mathematics teachers’ in Nigeria. The results of confirmatory factor analysis (CFA) support the adequacy of the values inculcation measures across gender and academic qualifications of mathematics teachers.